Microwave assisted enzymatic transesterification of waste cooking oil & rubber seed oil - Liyana, Amer Shah (2014)
This thesis presents biodiesel production from rubber seed oil via enzymatic process using Immobilized Lipase Candida Rugosa. The objectives of this study is to produce biodiesel fuels from waste cooking oil and rubber seed oil that comply with ASTM standard under optimum conditions of transesterification process such methanol to oil ratio, reaction temperature, mixing speed and microwave power using commercial and purpose made Immobilized Lipase Candida Rugoas enzyme in microwave reactor. This research also focus on production of biodiesel economically from non-edible renewable resources which using rubber seed oil and waste cooking oil as raw material instead of edible oil that competed with food sources. From the screening of three type of reactors, which were batch, microwave and ultrasonic, microwave reactor produced highest methyl ester in enzymatic transesterification. Microwave irradiation was applied in immobilization process. of Lipase Candida Rugosa enzyme was immobilized onto silica gel by crosslinking immobilization. The enyzme loading of using cross-linking method in this study was 47 % which is lower than reported by other researchers but the enzyme activity of purpose made immobilized lipase enzyme was 33 % higher than commercial immobilized lipase enzyme. From the parameter study of enzymatic transesterification process of waste cooking oil in microwave reactor, the optimum conditions were 6:1 methanol to oil ratio, 40°C reaction temperature, 150 rpm of mixing speed and 100 W microwave power. Enzyme leaching and enzyme recyclability has also been studied. Microwave irradiation increased the methyl ester production but, 25 % of this work immobilized enzyme was leached from silica support and reduced 21 % of its activity after 8 cycles. Compared with commercial immobilized lipase enzyme, purpose made immobilzied lipase enzyme showed higher stability. The purpose made immobilized enzyme than was been tested in transestrification process of palm oil, rubber seed oil and waste cooking oil. The resuls shows that the palm oil produced highest methyl ester, followed by rubber seed oil and waste cooking oil. 99 % of methyl ester was successfully produced using crude rubber seed oil, 1 wt. % purpose made immobilized lipase enzyme with 6:1 methanol to oil ratio, 40°C reaction temperature, 150 rpm of mixing and 100W of microwave power irradiation. The results also complied with ASTM standard and produced significant data.